Imagined Geographies : Central European Spatial Narratives between 1984 and 2014. - Konarzewska, Aleksandra; Baran-Szołtys, Magdalena; Glosowitz, Monika (La Vergne : Ibidem Press, 2018)
In 1984 Czech writer Milan Kundera published his essay 'The Tragedy of Central Europe' in The New York Review of Books, which established the framework for disputes about the space?between East and West? for the following 30 years. Even today, the echo of those debates is still audible in spatial narratives. Discussing the way in which literary figures are positioned within new hierarchies such as gender, class, or ethnicity, this volume shows how the space of the imagined Central Europe has been de- and reconstructed. Special attention is paid to the role of the past in shaping contemporary spatial discourse.
Intro; Content; Acknowledgements; Introduction. Central Europe and its 30 Good Years (1984-2014); A Narrative Construction: The Idea of Central Eruope in Milan Kundera's Writings; Galicia: An Eastern or a Western Land? Remarks on Locating the Province in the Framework of the East-West Opposition; Andrzej Stasiuk's Galician 'Middle Europe': Half-Dark, Empty, and Boundless; Longing for the Empty Space-Nostalgia and Central Europe; Author Information; Illustrations; Index of Names; Index of Subjects.
Print version record.
Includes bibliographical references and indexes.
eBooks on EBSCOhost
Keywords: East European literature -- History and criticism; Littérature est-européenne -- Histoire et critique; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; East European literature; Criticism, interpretation, etc